Salud mental y sus consecuencias en el estilo de vida de un cuidador de persona con discapacidad - Lopez Jimenez, Evelin Fernanda (2020)
The present case study is based on “Mental health and its consequences on the lifestyle of a caregiver of a person with disabilities”, mental health is a matter of real importance but nevertheless when the Ministries or Organizations carry out planning this issue is not considered within these schedules. Those who fulfill the role of caregivers of people with disabilities are usually women, relatives who have a strong bonding bond such as: Mother, wife, daughter. Zarit mentions that caregivers of people with disabilities live with overload for the tasks they perform daily adding to this the care they provide to their family member with disabilities, resulting in a great impact of stress that in turn can have repercussions on the different areas that develop as: family, work, social. The consequences of fulfilling this role, for the caregiver is not very evident because they state that they provide the necessary attention for love to their family member, and in most cases they forget their own life. That is why the caregiver who has been taken as a sample has been evaluated and a therapeutic scheme has been created to improve her quality of life